2014
DOI: 10.4028/www.scientific.net/amr.941-944.1445
|View full text |Cite
|
Sign up to set email alerts
|

Method for Determining the Plastic Properties of Metallic Materials by Instrumented Indentation with Dual Pyramidal Indenters

Abstract: Method for determining the plastic properties of metallic materials was proposed based on the functional relationships between representative stress, representative strain and nominal hardness which were established with the aid of dimensional analysis and finite element simulation. The errors of 0.2% yield strength and strain hardening exponent of five engineering metals were from-17.1% to 15.4% and from -0.125 to 0.11, respectively,which satisfied the need of engineering application and verified the effectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Doctor Lu Zhi-ke, from State key laboratory of nonlinear mechanics, Chinese Academy of Sciences, did the investigation about the research progress on residual stress measurement using instrumented indentation and proposed some possible remedies to the disadvantages of instrumented method 3 . Doctor Chen wei proposed the method for determining the plastic propertied by the ratio of indentation works and verified the effectiveness 4 . Kang Seung-Kyun did the research about instrumented indentation hardness on 24 metals and showed test's error 5 .…”
Section: Introductionmentioning
confidence: 89%
“…Doctor Lu Zhi-ke, from State key laboratory of nonlinear mechanics, Chinese Academy of Sciences, did the investigation about the research progress on residual stress measurement using instrumented indentation and proposed some possible remedies to the disadvantages of instrumented method 3 . Doctor Chen wei proposed the method for determining the plastic propertied by the ratio of indentation works and verified the effectiveness 4 . Kang Seung-Kyun did the research about instrumented indentation hardness on 24 metals and showed test's error 5 .…”
Section: Introductionmentioning
confidence: 89%